Activation of Imd pathway in hemocyte confers infection resistance through humoral response in Drosophila. - Nelson, B.; Freisinger, T.; Ishii, K.; Okado, K.; Shinzawa, N.; Fukumoto, S.; Kanuka, H. (Biochemical and Biophysical Research Communications, 2013)
Upon microbial invasion the innate immune system of Drosophila melanogaster mounts a response that comes in two distinct but complimentary forms, humoral and cellular. A screen to find genes capable of conferring resistance to the Gram-positive Staphylococcus aureus upon ectopic expression in immune response tissues uncovered imd gene. This resistance was not dependent on cellular defenses but rather likely a result of upregulation of the humoral response through increased expression of antimicrobial peptides, including a Toll pathway reporter gene drosomycin. Taken together it appears that Imd pathway is capable of playing a role in resistance to the Gram-positive S. aureus, counter to notions of traditional roles of the Imd pathway thought largely to responsible for resistance to Gram-negative bacteria.